Transfer RNA-dependent cognate amino acid recognition by an aminoacyl-tRNA synthetase. - Hong, K W (1996)
An investigation of the role of tRNA in the catalysis of aminoacylation of Escherichia coli glutaminyl-tRNA synthetase (GlnRS) has revealed that the accuracy of specific interactions between GlnRS and tRNAGln determines amino acid affinity. Mutations in GlnRS at D235, which makes contacts with nucleotides in the acceptor stem of tRNAGln, and at R260 in the enzyme's active site were found to be independent during tRNA binding but interactive for aminoacylation. Characterization of mutants of GlnRS at position 235, showed amino acid recognition to be tRNA mediated. Aminoacylation of tRNA(CUA)Tyr [tyrT (UAG)] by GlnRS-D235H resulted in a 4-fold increase in the Km for the Gln, which was reduced to a 2-fold increase when A73 was replaced with G73. These and previous results suggest that specific interactions between GlnRS and tRNAGln ensure the accurate positioning of the 3' terminus. Disruption of these interactions can change the Km for Gln over a 30-fold range, indicating that the accuracy of aminoacylation is regulated by tRNA at the level of both substrate recognition and catalysis. The observed role of RNA as a cofactor in optimizing amino acid activation suggests that the tRNAGln-GlnRS complex may be partly analogous to ribonucleoprotein enzymes where protein-RNA interactions facilitate catalysis.